(untitled) (Philological Studies, 2019)
Kriva Palanka (a town in the north-eastern part of Macedonia) is a twocomponent name of kriva (=reka) “curved river”, and palanka “a small town”. According to historical data, the town was originally called Kriva Reka, and then Kriva Reka Palanka. During the Ottoman Empire, the town was called Egri Dere (a Turkish translation of the Slavic name), and then Egri Dere Palanka. In medieval times, the upper part of Kriva Reka was called Sarandapor “40 ships”. The turks called it Krk Gecid (a translation of the greek name). In relation to this, in this study we make comparisons of hydronyms and toponyms.